(untitled) (Medical Forum Monthly, 2026)
Objective: This study aimed to assess the knowledge, attitudes, and perceptions of dental specialists in Saudi Arabia regarding the use of artificial intelligence (AI) programs in radiological diagnosis. Study Design: Cross sectional observational studyPlace and Duration of Study: This Online questionnaire survey were sent from the College of Dentistry-Ar Rass Branch, Qassim university and responses were collected from August 2023 till the end of March 2024. Methods: The total number of participants in the study were 145 (n=145). Primary data was collected through Questionnaire consisting of a 12-item close ended questions and quantitative methods(Chi-square test) was applied for analysis. Results: The survey included 145 recent graduates, mostly aged 25–30 years. Most participants already knew about AI (81.4%) and its use in OMFR (72.4%), and many supported using it in clinics (71.7%). Many felt the software cannot exceed a radiologist’s skill (62.1%) and would not accept an AI diagnosis that conflicts with their judgement (58.6%). Most believed AI will help new dentists (73.1%) and saw a future for it in oral radiology in Saudi Arabia (80%). Conclusion: AI applications has become more common in every field and dentistry is no exception. This study reveals that recently graduated dental professionals are more favourable towards the integration of AI applications in Oral Radiology in the Kingdom of Saudi Arabia (KSA)